Entrepreneurial Personality as a Moderator in the Relationship between Financial Attitudes and Financial Knowledge on Financial Management Behavior - Rosiana, Rosiana; Utomo, Mohamad Nur; Loong, Ang Hong; Sondoh, Stephen Laison; Sidin, Julian Paul; Gulabdin, Shaierah (Advances: Jurnal Ekonomi & Bisnis, 2025)
Purpose: This study examines the moderating role of entrepreneurial personality in the relationship between financial attitude, financial knowledge, and financial management behavior among MSME actors in Tarakan City. Research Design and Methodology: Data were collected from 130 MSME respondents using a quantitative approach with purposive sampling. The analysis employed Structural Equation Modeling (SEM) with WarpPLS version 8.0 software to assess direct and moderating effects. This analysis includes outer and inner model evaluations to test the reliability, validity, and significance of the relationships between variables and the moderating effects of entrepreneurial personality. Findings and Discussion: The findings reveal that financial attitudes and knowledge significantly and positively impact financial management behavior. However, entrepreneurial personality does not significantly moderate the relationship between financial attitude and financial management behavior. On the other hand, it substantially moderates the relationship between financial knowledge and financial management behavior in a negative direction. This suggests that individuals with strong entrepreneurial traits tend to rely more on intuition and experience, weakening the influence of financial knowledge on their financial behavior. Implications: The study implies that improving financial behavior among MSMEs should focus on enhancing knowledge and attitude and aligning entrepreneurial traits with sound financial practices through integrated training and mentoring programs.